Animating Eco-Conscious Living: Digital Walkthroughs as Communication Tools for Social Change in Urban Housing Speech - Hervina Dyah Aprilia; Arsa Widitiarsa Utoyo; Yunida Sofiana; Amarena Nediari (Center for Southeast Asian Social Studies (CESASS), 2026)
With increasing urbanization, the demand for sustainable and adaptable housing continues to rise, requiring innovative design approaches that maximize spatial efficiency while supporting sustainable living practices. This research investigates the use of digital walkthrough animation as a tool for communicating and evaluating sustainable urban housing design. Rather than employing animation solely as a representational medium, the study explores its potential to narrate and advocate ergonomic spatial optimization, eco-interior principles, and efficient urban living. A Design-Based Research (DBR) approach was employed to develop a 36 m² compact housing prototype integrating behavioral ergonomics and eco-sustainable interior design principles, which was subsequently translated into a digital 3D walkthrough animation. The animated walkthrough and representative model were evaluated through a design critique involving experts in behavioral ergonomics, eco-sustainability, and interior design, alongside semi-structured interviews assessing the effectiveness of animation as a communicative and evaluative tool. Findings revealed that animated walkthroughs conveyed spatial relationships and user interactions more effectively than conventional drawings or static 3D models, while also enhancing the clarity of spatial storytelling and the communication of ergonomic and ecological design concepts. The study demonstrates that digital walkthrough animation can foster stronger audience engagement by simulating experiential narratives of space and sustainable living. By bridging visual rhetoric, eco-interior design, and environmental communication, this research positions digital walkthrough animation as both a design appraisal method and a communication-for-social-change tool capable of supporting inclusive, sustainable, and future-oriented urban housing design.